Restoring Balance : Bangladesh's Rural Energy Realities - Asaduzzaman, M.; Barnes, Douglas F.; Khandker, Shahidur R. (World Bank, Washington, DC, 2014)
This study, the first to concentrate on Bangladesh's energy systems and their effects on the lives of rural people, drew on these background studies, as well as other World Bank-financed research on IAP and rural infrastructure, to present a rural energy strategy for the country. The study's broad aim was to identify ways to improve the living standard in rural Bangladesh through better and more efficient use of energy, while creating an environment conducive to growth and poverty reduction. For any developing country, the crux of a rural energy strategy is to have more and better choices for meeting rural demand for energy through market mechanisms and sound policy. This goes hand in hand with the development of competent implementing institutions, which are critical to the process. Also important are new supply- and demand side technologies that can be used to raise rural people's welfare and improve productivity to increase growth prospects. Accordingly, the rural energy strategy advocated by this study aims to satisfy the types of demand that increase household welfare and raise rural growth prospects as energy becomes a direct input into the production process.